Strategic knowledge management: In search of a knowledge-based organizational model - Alvarenga Neto,Rivadávia Correa Drummond de (2008)
This paper discusses the results and propositions of organizational knowledge management research conducted in the period 2001-2007. This longitudinal study had the unique goal of investigating and analyzing Knowledge Management (KM) processes effectively implemented in world class organizations. The main objective was to investigate and analyze the conceptions, motivations, practices, metrics and results of KM processes implemented in different industries. The first set of studies involved 20 world cases related in the literature and served as a basis for a theoretical framework entitled KM Integrative Conceptual Mapping Proposition. This theoretical proposal was then tested in a qualitative study in three large organizations in Brazil. The results of the qualitative study validated the mapping proposition and left questions for new research concerning the implementation of a knowledge-based organizational model strategy.